SKRINING, PENGOBATAN SERTA EDUKASI DIET SEHAT PENYAKIT JANTUNG DAN KARDIOVASKULAR PADA POSYANDU LANSIA KURANJI - Yusti Siana; Dian Puspita; Mhd Nurhuda (Nusantara Hasana Journal, 2025)
Hypertension is a disease that is a silent killer. A person suffers from hypertension if Systolic blood pressure ≥ 140 mmHg and/or Diastolic blood pressure ≥ 90 mmHg. This disease can increase blood vessel constriction and cause complications in the form of damage to a target organ such as stroke, coronary heart disease,) and other diseases such as diabetes mellitus. The elderly is an advanced stage of a life process characterized by a decrease in the body’s ability to adapt to environmental stress and an increase in morbidity due to susceptibility to diseases caused by blood vessels and heart disorders. Method: Counseling, treatment, and healthy diet education about heart and cardiovascular disease by the RSI Siti Rahmah team of heart specialists to the Kuranji Elderly Posyandu Community in Padang City at Rumah Gadang Baiturrahmah / Rumah Bagonjong Baiturrahmah. Results: Counseling, treatment, and education about a healthy diet for heart and cardiovascular disease went smoothly, and more than 50 older adults attended. Before treatment, older people receive an examination in the form of screeningfor blood pressure, blood sugar, uric acid, and cholesterol. Patients who are indicated to be suffering from heart disease will undergo an ECG examination. Conclusion: The importance of screening, treatment, and education on healthy diets for heart and cardiovascular disease to reduce high morbidity and mortality rates in the elderly.